2021
DOI: 10.1016/j.chest.2021.04.069
|View full text |Cite
|
Sign up to set email alerts
|

Delivering a Novel Medical Education “Escape Room” at a National Scientific Conference: First Live, Then Pivoting to Remote Learning Because of COVID-19

Abstract: Escape Rooms are gaining prominence as education modalities; the use of principles of game design have been shown to augment knowledge acquisition in a fun, team-based learning experience ("edutainment"). In this report, we outline some of the medical literature and then provide our step-by-step approach and lessons learned when building what was, to our knowledge, the first continuing medical education Escape Room at a national scientific meeting.We then comment on how this innovative educational offering was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…There are a couple of studies that described their experience and adaptation of virtual interactive learning during COVID-19. Most of these studies found a similar perception of VERs to previously documented perceptions of live-escape rooms [ 17 , 18 , 19 , 20 , 21 , 22 ]. However, none of these virtual escape rooms covered pharmacotherapy courses.…”
Section: Introductionsupporting
confidence: 68%
“…There are a couple of studies that described their experience and adaptation of virtual interactive learning during COVID-19. Most of these studies found a similar perception of VERs to previously documented perceptions of live-escape rooms [ 17 , 18 , 19 , 20 , 21 , 22 ]. However, none of these virtual escape rooms covered pharmacotherapy courses.…”
Section: Introductionsupporting
confidence: 68%
“…Escape rooms, since their inception in Japan in 2007, are a popular type of adventure game in which a team of players discover clues and solve puzzles in order to accomplish a goal within an allotted time. Recently, there has been a rise in introducing "Escape Rooms" in medical education [10][11][12][13]. Nonetheless, there is a paucity of literature regarding the use of "Escape Rooms" in the assessment of medical students' clinical skills.…”
Section: Introductionmentioning
confidence: 99%
“…Another example that could be used to meet the objective of the analysis is described by Kaul et al who created a puzzle that required learners to correctly turn multiple wheels to align clinical history, exposure, and imaging findings of interstitial lung disease. 34 Objective 5: Evaluate A further domain of Bloom's Taxonomy is "evaluation." Learners commonly learn how to critique and evaluate research during their training.…”
Section: Puzzle Typesmentioning
confidence: 99%
“…Another example that could be used to meet the objective of the analysis is described by Kaul et al who created a puzzle that required learners to correctly turn multiple wheels to align clinical history, exposure, and imaging findings of interstitial lung disease. 34…”
Section: Objective 4: Analyzementioning
confidence: 99%